Transcriptome changes associated with muscle and intramuscular connective tissue growth in cull cows under different recovery gain rates - Fausto, Daiane Aparecida (2016)
The renewal rate of stromal and myofibrillar proteins defines muscle growth, and can affect the quality of meat, by affecting collagen turnover and proteolytic rate. There is a lack of information on changes in the muscle protein remodeling process in response to the recovery weight gain rate observed during \"realimentation\" after undernutrition, which may be altered in older animals. Changes in muscle tissue during the recovery period may be indicated by the differential expression profile of genes after RNA sequencing. The objectives of this study were to evaluate transcriptome changes in the muscle of Nellore cull cows subjected to: 1) recovery weight gain under grazing conditions; and 2) recovery from undernutrition at different weight gain rates. In the first experiment, the animals were divided into two groups and subjected to one of two nutritional managements under grazing conditions: maintenance (maintenance of weight and high body condition score under grazing conditions) and recovery gain (recovery from low body condition score with moderate body weight gain of 0.6 kg/day under grazing conditions). In the second experiment, the animals were divided into three groups and subjected to one of three nutritional managements under feedlot conditions: control (slaughtered at low body condition score), moderate recovery gain (MG; 0.6 kg of daily live weight gain) during the dry season, and high recovery gain (HG; 1.2 kg of daily live weight gain) during the dry season. In both experiments, samples of longissimus dorsi muscle were collected after slaughter and immediately frozen until sequencing analysis could be performed. In the first experiment, genes related to inflammatory response, such as semaphorin 4A (SEMA4A), solute carrier family 11 member 1 (SLC11A1), ficolin-2 (FCN2), and placental growth factor (PGF), were expressed at higher levels during recovery gain. In the second experiment, osteonectin (SPARC) and collagen type IV subunits 1 (COL4A1) were expressed at higher levels in both recovery gain and connective tissue remodeling. For MG, structural myofibrillar proteins such as myosin IE (MYO1E), myosin, heavy chain 11 (MYH11), myogenin (MYOG), and actinin, alpha 4 (ACTN4) were identified. In the HG treatment, the B-cell CLL/lymphoma 9 (BCL9), peroxisome proliferator-activated receptor alpha (PPARA), diacylglycerol O-Acyltransferase 2 (DGAT2), and phosphatidylinositol 4-Kinase, catalytic, and beta (PI4KB) genes indicated more deposition of adipose tissue. In summary, we observed that muscular deposition during recovery weight gain involved the regulation of expression of several genes related to the extracellular matrix (ECM), corroborating the inflammatory and -like models observed in mature animals. Moreover, in the HG group, genes related to collagen synthesis and fat deposition were also found, indicating the important contribution of connective tissue during muscle growth. These results are important for understanding tissue development as a whole, and will assist in the progress of scientific knowledge on muscle remodeling during recovery weight gain and its influence on protein structures and intracellular routes.